Diagnosis of the Technical Condition of Historic Tenement Houses as the First Stage of Revitalisation of the City - Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Revitalisation of degraded downtown areas is a problem for many cities and towns in Europe. All spatial, economic and social changes result from the expectations of residents together with technical needs. The scope of revitalisation activities results from the diagnosis of the technical condition of the degraded part of the city. The article presents a sample assessment of the technical condition of a tenement house in Kożuchów located within a downtown complex covered by revitalisation plans.
Keywords: revitalisation; technical condition assessment; technical wear degree; historic building; rewitalizacja; ocena stanu technicznego; stopień zużycia technicznego; budynki zabytkowe